2023
DOI: 10.1111/ele.14193
|View full text |Cite
|
Sign up to set email alerts
|

Physiological tipping points in the relationship between foraging success and lifetime fitness of a long‐lived mammal

Abstract: Although anthropogenic change is often gradual, the impacts on animal populations may be precipitous if physiological processes create tipping points between energy gain, reproduction or survival. We use 25 years of behavioural, diet and demographic data from elephant seals to characterise their relationships with lifetime fitness. Survival and reproduction increased with mass gain during long foraging trips preceding the pupping seasons, and there was a threshold where individuals that gained an additional 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The same pattern has been found in seals [ 9 ] and birds [ 29 ]. For reproductively successful elephant seals, delaying moult could mean a shorter foraging trip afterwards, during the crucial period when females are diving nearly continuously and consuming thousands of fish daily [ 31 , 50 ] to support gestation and prepare for the upcoming lactation period [ 51 ]. The relative synchrony of haul-out timing but asynchrony of moult timing could mean that predator aggregation potential is still high, as other studies have found [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The same pattern has been found in seals [ 9 ] and birds [ 29 ]. For reproductively successful elephant seals, delaying moult could mean a shorter foraging trip afterwards, during the crucial period when females are diving nearly continuously and consuming thousands of fish daily [ 31 , 50 ] to support gestation and prepare for the upcoming lactation period [ 51 ]. The relative synchrony of haul-out timing but asynchrony of moult timing could mean that predator aggregation potential is still high, as other studies have found [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding activity can determine the animal's distribution (Fortune et al 2020), reproductive success (Beltran et al 2023), food availability (Billard et al 2020), as well as evolutionary patterns through niche specialization (Dehnhard et al 2020). Therefore, understanding the feeding activity, particularly that of a threatened organism such as a manta ray, may promote its conservation management effectively.…”
Section: Introductionmentioning
confidence: 99%